Golden Standard or Obsolete Method? Review of ECG Applications in Clinical and Experimental Context - Stracina, Tibor; Ronzhina, Marina; Redina, Richard; Novakova, Marie (Frontiers in Physiology, 2022)
Cardiovascular system and its functions both under physiological and pathophysiological conditions have been studied for centuries. One of the most important steps in the cardiovascular research was the possibility to record cardiac electrical activity. Since then, numerous modifications and improvements have been introduced, however, electrocardiogram still represents a golden standard in this field. The paper overviews possibilities of ECG recordings in research and clinical practice, deals with advantages and disadvantages of various approaches and summarizes possibilities of advanced data analysis. Special emphasis is given to state-of-the-art deep learning techniques intensely expanded in wide range of clinical applications and offering promising prospects in experimental branches. Since according to the World Health Organization, cardiovascular diseases are the main cause of death worldwide, studying of electrical activity of the heart is still of high importance both for experimental and clinical cardiology.